2016
DOI: 10.1080/16546628.2017.1264710
|View full text |Cite
|
Sign up to set email alerts
|

Glucomannan- and glucomannan plus spirulina-enriched pork affect liver fatty acid profile, LDL receptor expression and antioxidant status in Zucker fa/fa rats fed atherogenic diets

Abstract: We evaluated the effects of glucomannan or glucomannan plus spirulina-restructured pork (RP) on liver fatty acid profile, desaturase/elongase enzyme activities and oxidative status of Zucker fa/fa rats for seven weeks. Control (C), glucomannan (G) and glucomannan/spirulina (GS)-RP; HC (cholesterol-enriched control), HG and HGS (cholesterol-enriched glucomannan and glucomannan/spirulina-RP) experimental diets were tested. Increased metabolic syndrome markers were found in C, G and GS rats. Cholesterol feeding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
6
0
2
Order By: Relevance
“…The algae employment as functional ingredients in different food matrices has also been studied [ 220 ]. Depending on the study matrix, the glucomannan plus Spirulina consumption has revealed different effects on carbohydrates homeostasis in Zucker fa/fa rats fed an atherogenic diet.…”
Section: Effects Of Algae Consumption On T2dm Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The algae employment as functional ingredients in different food matrices has also been studied [ 220 ]. Depending on the study matrix, the glucomannan plus Spirulina consumption has revealed different effects on carbohydrates homeostasis in Zucker fa/fa rats fed an atherogenic diet.…”
Section: Effects Of Algae Consumption On T2dm Pathophysiologymentioning
confidence: 99%
“…The inclusion of these functional ingredients in a fish product made with squid-surimi lowered blood glucose, leptin, and adiponectin levels [ 221 ]. In contrast, when glucomannan plus Spirulina was included in a meat matrix, no changes were revealed on glycemia [ 220 ]. This loss of effect could be due to the higher caloric content of the diets belonging to the study with functional meats, in which the functional ingredient did not show effect on blood glucose.…”
Section: Effects Of Algae Consumption On T2dm Pathophysiologymentioning
confidence: 99%
“…de elongación e insaturación de ácidos grasos en el hígado Algunas proporciones de productos y precursores se utilizaron como índices sustitutos de enzimas hepáticas utilizando las siguientes fórmulas 26 : Δ6 elongasa-desaturasa: (a) Ácido docosahexahenoico /ácido linolénico (C22:6 n-3/C18:3 n-3) (b) Ácido araquidónico/ácido linoleico (C20:4 n-6 / C18:2 n-6) Estearoil-CoA: ácido palmitoleico/ácido palmítico (C16:1 n-7/C16:0) Oleoil-CoA: ácido oleico/ácido esteárico (C18:1 n-9/ C18:0) Δ5D: ácido araquidónico / ácido eicosatrienoico (C20: 4 n-6 / C20: 3 n-6) Δ6D: ácido gamma-linolénico /ácido linoleico (C18:3 n-6/C18:2 n-6)…”
Section: Relación Producto/precursor De Las Enzimasunclassified
“…La relación de producto/precursor de las enzimas está limitada por los ácidos grasos que se detectaron mediante la cromatografía. De acuerdo a los índices sustitutivos calculados, se observaron niveles bajos de las enzimas Δ-6elongasa-desaturasa y Oleyl-CoA, menos de 1,90 y 3,04 respectivamente, asociados al mecanismo de protección para evitar el exceso de ácidos grasos peroxidables y oxiesteroles en el hígado en el primer caso y la composición de la grasa hepática total en el segundo, por la inhibición parcial de la transformación de ALA a EPA y DHA o AL a ARA 26 .…”
Section: Vírgenesunclassified
“…The glucomannans could be an option for therapeutic tools in curing a wide range of physiological disorders such as diverticulitis and Crohn's disease or ulcerative colitis (Tester & Al-Ghazzewi, 2013). Furthermore, a study by González-Torres et al (2016) revealed that cholesterolemia was lower in glucomannan and glucomannan/spirulina treatment in rats. Glucomannan has been approved as generally regarded as safe (GRAS) food additive and had been approved by related agencies on food and health regulation in the USA, Canada and European Commission (Tester & Al-Ghazzewi, 2017).…”
Section: Introductionmentioning
confidence: 99%